Professional records and information management - Stewart, Jeffrey Robert; Melesco, Nancy M. (New York : Glencoe/McGraw-Hill, 2002)
The book discusses the profession of records and information management, managing nonelectronic records and electronic information management.
System requirements for disk: IBM-compatible PC; Windows 3.1 or Windows 95/98; harad disk drive.
Rev. ed. of: Professional records management, c1995.
Includes index.
rua 23/08/13, ijb 10/04/2019
Loans
Keywords: Electronic filing systems; Business records; Information resources management